Prevalence and factors associated with severe anaemia post-caesarean section at a tertiary Hospital in Southwestern Uganda - Sylvie Atosa Sivahikyako; Asiphas Owaraganise; Leevan Tibaijuka; David Collins Agaba; Musa Kayondo; Joseph Ngonzi; Julius Mugisha; Hamson Kanyesigye (BMC, 2021)
Abstract Background Severe anaemia after caesarean section adversely affects the woman and the new-born. While prenatal anaemia is extensively studied, the literature on post-caesarean section anaemia is limited and characteristics of women at the highest risk of developing severe anaemia after caesarean section are unknown. This study aimed to determine the prevalence and factors associated with severe anaemia on day three post caesarean section. Methods On the third day after caesarean section, women were consecutively enrolled in a cross-sectional study at Mbarara Regional Referral Hospital (MRRH). Women who got transfused peripartum were excluded. For every woman, we measured haemoglobin (Hb) concentration and collected data on sociodemographic, obstetric, and medical characteristics. The primary outcome was severe anaemia after caesarean section, defined as Hb < 7 g/dl. We used logistic regression analysis to determine factors associated with severe anaemia after caesarean section. P-value < 0.05 was considered statistically significant. Results From December 2019 to March 2020, 427 of 431 screened women were enrolled in the study. Their mean age was 26.05 (SD ± 5.84) years. Three hundred thirteen (73.3%) had attended at least four antenatal care visits. The prevalence of severe anaemia post-caesarean section was 6.79%. Foetus with macrosomia (aOR 7.9 95%CI: 2.18-28.85, p <  0.01) and having mild or moderate anaemia pre-caesarean section (aOR:9.6, 95%CI: 3.91-23.77, p <  0.01) were the factors associated with severe anaemia after caesarean section. Conclusion Severe anaemia in women post-caesarean section is relatively uncommon at our institution. It is associated with preoperative anaemia and macrosomic birth. Women with a low preoperative Hb concentration and those whose foetus have macrosomia could be targeted for haemoglobin optimisation before and during caesarean section.